A liquid-crystal-based immunosensor for the detection of cardiac troponin I. Issue 13 (20th May 2020) - Xia, Chunli; Zhou, Dong; Su, Yueming; Zhou, Guangkai; Yao, Lishuang; Sun, Weimin; Liu, Yongjun
Abstract : Cardiac troponin I (cTnI) is one of the most sensitive and specific markers of myocardial cell injury. In this study, a label-free biosensor that utilizes the birefringence property of liquid crystal (LC) for the detection of cTnI is demonstrated. Abstract : Cardiac troponin I (cTnI) is one of the most sensitive and specific markers of myocardial cell injury, which can detect even minor myocardial damages. It is recognized as the main biochemical marker of the rapid diagnosis of acute myocardial infarction (AMI) and acute coronary syndrome (ACS). In this study, a label-free biosensor that utilizes the birefringence property of a nematic liquid crystal (LC) for the detection of cTnI is demonstrated. A chemically sensitive film with specific molecular recognition ability was decorated on the surface of a substrate, and the LC molecules were arranged in a vertically oriented order under the influence of the sensitive film, and a dark background signal was obtained using a polarizing optical microscope. When the antigen–antibody specifically binds to form a stronger acting force, the orientation of the LC molecules changes, resulting in a bright optical appearance. This LC-based immunosensor not only has the advantages of a facile structure, low cost and excellent specificity but also high sensitivity (a low detection limit of 1 pg ml −1 ), and has a promising future in biomedical related fields.